The Successful Surgical Treatment of a Giant True Left Ventricular Aneurysm: a Case Report - Y. B. Brand; M. K. Mazanov; E. N. Ostroumov; M. A. Sagirov; N. I. Kharitonova; M. V. Chumakov; D. V. Chernyshev (Неотложная медицинская помощь, 2019)
We report the successful surgical treatment of a giant true thrombosed aneurysm of the left ventricle.A 59-year-old male patient Z. was admitted with severe heart failure and chronic thrombosed aneurysm of the left ventricle, formed after acute extensive myocardial infarction, despite successful installation of a stent into the anterior descending artery in the acute period. Echocardiography revealed a significant increase in the volume of the left ventricular cavity, a significant decrease in the contractile function of the left ventricular myocardium (ejection fraction 32-36%), a giant left ventricular aneurysm (9x6 cm) with a parietal lining thrombus in the aneurysm cavity. Coronary angiography showed an aneurysmal dilatation of the circumflex branch of more than 6 mm, hemodynamically significant stenosis of two coronary arteries. According to the scintigraphy, the myocardium beyond the scar tissue was viable. The patient underwent resection of a left ventricular aneurysm, endoventricular plasty (Dor procedure), coronary artery bypass surgery of the circumflex artery and obtuse marginal branch of the left coronary artery.The patient was discharged in satisfactory condition on day 14 after surgery. At follow-up 6 months after surgery, an increase in the ejection fraction to 3941% was noted.